2000
DOI: 10.1093/qjmed/93.10.677
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hip fracture risk factors in women aged 70 years and over

Abstract: We estimated the prevalence of common risk factors for hip fracture and the numbers needed to treat (NNT) to prevent a hip fracture in various high-risk population groups, using a postal risk factor survey of women aged 70 years and above from General Practices in Grampian and Yorkshire. Recorded risk factors included prior fracture of any type; low body weight; smoking; and family history of fracture. The prevalence rates of hip fracture risk factors were 34%, 7% and 11% for previous fracture, maternal hip fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…In the absence of having access to the primary data or a reported estimate of the ESR in the literature, the ESR can be estimated from two independent samples if the investigator knows the overall risk of disease and the relative risk (RR) of disease given the exposure of interest. There have been a number of published studies where ESRs have been calculated from two independent samples by multiplying the overall risk of disease from one sample by the RR from a second independent sample [1,2]. Stewart et al computed the ESR of hip fracture given certain exposures (prior fracture, family history of fracture, low body weight, and smoking) in persons over the age of 70 in the United Kingdom [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of having access to the primary data or a reported estimate of the ESR in the literature, the ESR can be estimated from two independent samples if the investigator knows the overall risk of disease and the relative risk (RR) of disease given the exposure of interest. There have been a number of published studies where ESRs have been calculated from two independent samples by multiplying the overall risk of disease from one sample by the RR from a second independent sample [1,2]. Stewart et al computed the ESR of hip fracture given certain exposures (prior fracture, family history of fracture, low body weight, and smoking) in persons over the age of 70 in the United Kingdom [2].…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of published studies where ESRs have been calculated from two independent samples by multiplying the overall risk of disease from one sample by the RR from a second independent sample [1,2]. Stewart et al computed the ESR of hip fracture given certain exposures (prior fracture, family history of fracture, low body weight, and smoking) in persons over the age of 70 in the United Kingdom [2]. This study found that the ESR of hip fracture among those with all 4 exposures was 8.9%.…”
Section: Introductionmentioning
confidence: 99%
“…With an increasingly elderly and growing population, the number of osteoporotic fractures will steadily increase over the next few decades [1]. In the UK over the next 40 years, the number of people over 60 years will rise by around 50%, and the number of those over 90 years of age will double [2].…”
Section: Introductionmentioning
confidence: 99%
“…suggest that if strategies aimed at preventing hip fracture are to be productive, then they should be targeted at subgroups that are at an increased risk of fracture rather than the entire osteoporosis population [25]. To identify patients at high risk of hip fracture, it is necessary to know which risk factors are important and the magnitude of the fracture risk [30].…”
Section: Identification Of Those At Riskmentioning
confidence: 99%
“…The increasing number of therapeutic options for fracture prevention require targeting towards high-risk groups if they are to be cost-effective [30]. Where health-service resources are limited, applying secondary prevention to high-risk groups may be more feasible economically than treating a less narrowly defined population [25].…”
Section: Treatment/fracture Preventionmentioning
confidence: 99%